DAMPAK COVID-19 TERHADAP RANTAI PASOK PERUSAHAAN APPLE INC DI TIONGKOK TAHUN 2019-2023 - Wati, Jihan Tri Imelda; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Covid-19 is an infectious disease caused by a novel coronavirus named SARS-CoV-2. It was first identified in Wuhan City, Hubei Province, China, in December 2019. The Covid-19 pandemic has significantly impacted the continuity of operations for multinational corporations, particularly those heavily reliant on global supply chains and manufacturing in China. This study examines the case of Apple Inc., where the pandemic has profoundly affected its supply chain, which depends largely on manufacturing hubs in China, especially key partner factories such as Foxconn and Pegatron. Lockdown policies and mobility restrictions led to decreased production capacity, component shortages, shipment delays, and disruptions in the distribution of products to global markets. The health-related restrictions compelled Apple to adapt its operations by strengthening supplier diversification and expanding its manufacturing base to other countries to mitigate the risks of production concentration in a single location. Dunning’s eclectic theory provides a crucial framework for understanding Apple Inc.’s supply chain management strategy during the pandemic. The theory comprises three main components. First, ownership advantage, which refers to the proprietary assets a firm possesses, such as technology, brand, and innovation, that confer unique competitive advantages. Second, location advantage, which encompasses benefits derived from the production site, including robust infrastructure, low-cost skilled labor, and reduced operational expenses. Third, internalization advantage, which involves the firm's benefits from directly managing production processes rather than outsourcing, thereby maintaining greater control and efficiency. This theory elucidates how Apple systematically and structurally managed to sustain its operations and innovate amid a global crisis. Keywords: Apple Inc, Economy, Covid-19 Pandemic, Supply Chain.